Respuesta :

Answer:

Input-previous input then multiply this difference by 3, add the squared difference to the previous output to get the current output

Step-by-step explanation:

The first output is predetermined then the subsequent outputs are obtained by subtracting previous input from previous output then we multiply the difference by 3 and add to the previous output for example

[tex]{(7-4)\times 3}+32=9+32=41[/tex]

[tex]{(10-7)\times 3}+41=9+41=50[/tex]

[tex]{(12-10)\times 3}+50= 6+50=56[/tex]

ACCESS MORE